IMPLEMENTASI APLIKASI POINT OF SALE (POS) BERBASIS MOBILE WEB UNTUK MENDUKUNG TRANSAKSI TOKO SEPATU 45 - Kasmi, Kasmi; Al-Awabin, Abde Fadli; Dede, Dede (STMIK Pringsewu, 2025)
This research focuses on the implementation of a mobile web-based Point of Sale (PoS) application to support transactions at Toko Sepatu 45. The store faces challenges in managing transactions, stock recording, and creating sales reports manually, which affects efficiency and data accuracy. Therefore, a technological solution is needed to improve productivity and reduce errors in transaction management. This mobile web-based PoS application is designed to facilitate store owners in recording sales, managing stock, and generating automatic and real-time sales reports. The system development uses the Waterfall method, which includes requirement analysis, system design, implementation, and testing. The testing results using blackbox testing include successful tests for the login page, navigation menu buttons, product data input, product data output, and product sales invoices. Through this research, it is expected that the mobile web-based Point of Sale application can be used to streamline operational activities at Toko Sepatu 45, including transaction processes such as purchasing and selling, as well as simplifying the recap of reports such as purchase and sales reports.